Privacy Integrated Queries - McSherry, Frank (Communications of the ACM, 2010)
Privacy Integrated Queries (PINQ) is an extensible data analysis platform designed to provide unconditional privacy guarantees for the records of the underlying data sets. PINQ provides analysts with access to records through an SQL-like declarative language (LINQ) amidst otherwise arbitrary C# code. At the same time, the design of PINQ’s analysis language and its careful implementation provide formal guarantees of differential privacy for any and all uses of the platform. PINQ’s guarantees require no trust placed in the expertise or diligence of the analysts, broadening the scope for design and deployment of privacy-preserving data analyses, especially by privacy nonexperts.